Proposta de ensino de leitura e escrita, por meio de discriminações condicionais aplicadas com software, para jovens e adultos de um curso de EJA - Santos, Carlos Alberto Daniel dos (2011)
The present study has had as goal the application and valuation of a suggestion of reading and writing teaching, for students with a history of scholar failure, and that attend the education for young and grown-ups at a private school of the city of São Paulo. The teaching was applied to 11 participants (partakers), during the normal period of class, in the collective context. After the valuation of the previous repertories of reading and writing, the teaching of words programming, formed by simple and complex syllables was applied. The training, accomplished with help of Master software, and consisting of relations among dictated words (A) figures (B) and written words (C) of relations among (written and dictated) words and letters (relations entitled CE and AE) of relation between written syllables and letters (relation entitled CEsyllables). The taught relations were: AB, BC, CB, AC, CE, CE-syllables and AE. After training of different relations tests were given in order to verify if it would emerge the not trained relations CD (expressive reading) and AF (manuscript writing). Tests of reading and writing generalization also were accomplished as well as of words composite by simple and complex syllables and with phrases. The results revealed that the teaching programming improved the performance of all participants since all of them presented generalized reading and writing of words and greater number also presented generalized reading of phrases; while in writing phrases the results indicated that all the participants have iniciated the process of acquisition of this repertory. The results signalized that the proposal of teaching has been efficient specially for reading repertory; if before the teaching the participants in their most, were not able to read at lest words, after the teaching, all of them have done the correct reading words, and also, most of them began reading phrases. Nevertheless, concerning the writing repertory, the positive effect was more restricted, since the participants have gotten to improve writing of words, showing yet difficulty of writing phrases. However not having gotten the domain of reading phrases, the improvement occurred with those that participated, show clearly that the reading and writing teaching, by means of conditional discrimination together with the use of Educative Software is efficient and may be applied to those students that attend the course of EJA